Bit error rate performance analysis of TCM-8PSK system based on band-limited nonlinear satellite channel - LI Jing1; LIU Zhen-fang3; LI Ai-hong2; SHEN Rong-jun2 (Tongxin xuebao)
The performance of error probability for TCM-8PSK over the band-limited nonlinear satellite channel was de-rived firstly.Then,the dynamic simulation tool—— Simulink included in Matlab was used to simulate and verify the derivation result and the optimal working point for QPSK and TCM-8PSK were found under the condition of Saleh nonlinear model.Finally,the equalization algorithm used to improve the effects of nonlinear distortion was presented and at the same time the performance was simulated.The results of derivation and simulation show that it is necessary to study of TCM-8PSK for nonlinear satellite channel.